2010
DOI: 10.1007/s10705-010-9348-6
|View full text |Cite
|
Sign up to set email alerts
|

Critical N concentration can vary with growth conditions in forage grasses: implications for plant N status assessment and N deficiency diagnosis

Abstract: The N nutrition index (NNI, defined as the actual shoot N concentration relative to a reference critical value, N ref ) is a valuable tool to analyze the N nutrition status of crops. We present empirical evidence obtained for a range of forage grass species and environmental conditions with the aim to contribute to verify the NNI as a tool to diagnose N deficiency and to examine responses to N fertilization. Ten N fertilization experiments were conducted in the SE of the Pampa region (Argentina) and included (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 26 publications
2
20
0
5
Order By: Relevance
“…Since most observed data have had fertilizer treatment applied (i.e., reducing or removing N limitation), it is likely that the Lemaire-cutting method overestimates critical N uptake. Agnusdei et al (2010) also found the Lemaire reference curve to provide much higher N uptake values than critical N uptake derived from experimental data. By incorporating calibrated N dilution curves along with biomass yield and N concentration information at each cut, these methods move toward more realistic critical N uptake values.…”
Section: Critical N Uptake Methods and Observed Valuesmentioning
confidence: 84%
“…Since most observed data have had fertilizer treatment applied (i.e., reducing or removing N limitation), it is likely that the Lemaire-cutting method overestimates critical N uptake. Agnusdei et al (2010) also found the Lemaire reference curve to provide much higher N uptake values than critical N uptake derived from experimental data. By incorporating calibrated N dilution curves along with biomass yield and N concentration information at each cut, these methods move toward more realistic critical N uptake values.…”
Section: Critical N Uptake Methods and Observed Valuesmentioning
confidence: 84%
“…El uso de este insumo, ha demostrado ser una herramienta tecnológica de alto impacto para la producción de forraje en ambientes ganaderos de la Pampa Deprimida (Agnusdei, Assuero, Lattanzi y Marino, 2010), mejorando la eficiencia de uso de otros recursos, como por ejemplo el agua (Cooper, Gregory, Tully y Harris, 1987).…”
unclassified
“…En este experimento, realizado en primavera avanzada, se registró efecto del agregado de N sobre la BA de agropiro alargado coincidiendo con lo reportado para esta especie y otras que habitualmente se utilizan en la región (Marino y Agnusdei, 2007;Agnusdei et al, 2010;Errecart, Agnusdei, Latanzi y Marino, 2012). Por otra parte, se registró efecto significativo del sitio, coincidiendo con lo observado por Vázquez, Costa, Monterubbianesi y Godz (2001).…”
unclassified
“…Sin embargo, en la práctica, a especies tan bien conocidas como agropiro o festuca (entre otras) se les asigna escasa tecnología y difícilmente llegan a expresar su capacidad productiva (Agnusdei et al, 2010;Parsons et al, 2010). El alto potencial de estas especies estaría relacionado con su plasticidad en cuanto a las condiciones de suelo y clima, lo cual asegura una alta persistencia en comparación con otras especies .…”
Section: Introductionunclassified